Penegakan Hukum terhadap Terpidana Korupsi yang Tidak Membayar Uang Pengganti: Tinjauan Hukum Acara Pidana dan Undang-Undang Pemberantasan Korupsi - Muhammad Adhadin Azhar; Ummi Maskanah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the authority and constraints of the executing prosecutor in implementing the substitute money judgment and its implementation procedures according to the criminal procedure law in Indonesia. The research method used is normative juridical with a statute approach, a case approach, and a conceptual approach through library research techniques, namely by examining laws and regulations, court decisions, and relevant legal literature. The results of the study show that the authority of the prosecutor as an executor has been clearly regulated in Article 270 of the Criminal Code and Attorney General's Regulation Number 2 of 2017, but its implementation still faces obstacles in the form of concealment of assets, weak coordination between institutions, low economic value of confiscated goods, and the tendency of convicts to choose subsidiary crimes instead of paying compensation. This research has implications for the importance of strengthening the asset tracing system, coordination between law enforcement agencies, and optimizing execution mechanisms to improve the recovery of state losses and legal certainty. The limitations of this study lie in the use of normative juridical methods that have not described the empirical conditions thoroughly and are limited to the case study of Decision Number 70/Pid.Sus-TPK/2024/PN.Jkt.Pst. Based on the results of the study, it is recommended to strengthen regulations and mechanisms for tracking assets resulting from corruption, increase coordination between law enforcement agencies, and update the policy on the execution of substitute money so that the implementation of state loss recovery can be run more effectively and provide legal certainty.